The new spirit of hospitality : designing tourism futures in post-truth worlds - Tzanelli, Rodanthi, 1974- (Tourism security-safety and post conflict destinations., 2023)
A 'new spirit of hospitality' beckons planetary provenances of leisure and pleasure, to promote tourism destinations through the digitization and cinematic advertising of tourist experience. While releasing identities, populations, and environments from their geographical and political isolation, this new spirit may rob them of their ability to communicate cultural diversity on their own terms. Such changes also affect the professionals who produce aesthetic renditions of other people's home territories as tourist destinations, often feeding into domestic perceptions of homemaking, with various good and bad consequences for the design of sustainable planetary futures. Through methodological elaborations on case studies, Tzanelli explains that we have entered a new era of tourism and hospitality mobilities dominated by crises of cultural representation and host presence. Triggered by the urge to renovate concept design, the crisis leads to a proliferation of what is just, true, and real, with various consequences for those interest groups involved in the production of truthfulness, justice and reality in hospitality and tourism. The Tourism Security-Safety and Post Conflict Destinations series provides an insightful guide for policy makers, specialists and social scientists interested in the future of tourism in a society where uncertainness, anxiety and fear prevail.